ENVISION: Increasing diversity of a large phase 3b/4 confirmatory trial of aducanumab to better understand the efficacy and safety among historically underrepresented participants of Alzheimer's disease research and clinical trials. (20th December 2022) - Montenigro, Philip H.; Cheng, Wenting; O'Gorman, John; Murphy, Jennifer; Gillis, Cai; Maserejian, Nancy Nairi; Mascherino, Liz; Butts, Cherie; Ashraf, Daanish; Racine, Annie M; Aisen, Paul; Castrillo‐Viguera, Carmen; et al.
Abstract: Background: While Black/African Americans and Latinx/Hispanics have nearly twice the risk of developing Alzheimer's disease compared to Non‐Hispanic Whites, their involvement in clinical research and trials remains low. Due to the lack of data and underrepresentation in research, it is unknown if there are clinicopathological differences in Alzheimer's disease or response to therapies. We have established specific recruitment goals for underrepresented groups in the aducanumab Phase 3b/4 confirmatory ENVISION study, which is a multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study of participants with mild cognitive impairment and mild dementia stages of Alzheimer's disease (Stages 3 and 4; NCT05310071), designed to better understand the efficacy and safety of aducanumab treatment for these populations. Method: Epidemiological and clinical data by race/ethnicity in the United States (US) were obtained from systematic literature reviews and Clinical trial data were then used to characterize the clinicopathological profile of Alzheimer's disease among diverse groups. Data from underrepresented participants were pooled and analyzed contemporaneous Alzheimer's disease clinical trials to identify potential differences (i.e., heterogeneity) in clinical and biomarker outcomes. Result: Based on epidemiological analyses, the ENVISION has an enrollment target of 18% for patient populations historically underrepresented in clinical trials in the US. Limited pooled clinical trial data suggests there may be greater heterogeneity in clinical and biomarker endpoints in underrepresented groups. Conclusion: Research and clinical trial data from diverse patient populations with Alzheimer's disease are lacking. Inclusive research is essential to advancing the mission to develop treatments for this devastating disease. Data‐driven recruitment goals have been established and analyses planned to address the safety and efficacy of aducanumab in historically underrepresented populations in the ENVISION study. This could serve as a model for evaluating differences in treatment outcomes across racial/ethnic groups.